Peran Bakteri Bacillus Dan Pseudomonas Bagi Pertumbuhan Tanaman - Laia, Darman; Lase, Natalia Kristiani (Jurnal Ilmu Pertanian dan Perikanan, 2024)
Agriculture is a strategic sector that has the ability to overcome world problems, such as natural climate transition and land degradation. The use of Plant Growth-Promoting Rhizobacteria (PGPR), such as Bacillus and Pseudomonas, is one promising solution. These bacteria play a role in increasing nutrient uptake, controlling pathogens, and stimulating the development of cultivated products. Based on the results of previous research, it is explained that Bacillus spp. are able to produce bioactive metabolites that increase plant tolerance to stress, while Pseudomonas spp. play a role in increasing systemic plant immunity. The combination of the two is proven to have a synergistic effect, increasing plant productivity by up to 25%, and improving rhizosphere health. However, challenges such as lack of technology adoption and supportive policies still hinder the widespread implementation of PGPR. This research highlights the great potential of Bacillus and Pseudomonas as biological agents in supporting sustainable agriculture.